2017
DOI: 10.1371/journal.pone.0175220
|View full text |Cite
|
Sign up to set email alerts
|

Oral cavity hydrodynamics and drag production in Balaenid whale suspension feeding

Abstract: Balaenid whales feed on large aggregates of small and slow-moving prey (predominantly copepods) through a filtration process enabled by baleen. These whales exhibit continuous filtration, namely, with the mouth kept partially opened and the baleen exposed to oncoming prey-laden waters while fluking. The process is an example of crossflow filtration (CFF) in which most of the particulates (prey) are separated from the substrate (water) without ever coming into contact with the filtering surface (baleen). This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…While the baleen area primarily affects drag forces and the outflow speed after water is filtered through the baleen (Potvin & Werth, ; Werth & Potvin, ; Werth et al, ), the mouth opening area affects the inflow volume of prey‐laden water. The trade‐offs in the relationship between mouth friction drag, area and speed have been illustrated by Potvin and Werth (); we present the estimated open‐mouth friction drag relative to bowhead whales (i.e. scaled by gape area) and put these values in context with their resulting filtration rates (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the baleen area primarily affects drag forces and the outflow speed after water is filtered through the baleen (Potvin & Werth, ; Werth & Potvin, ; Werth et al, ), the mouth opening area affects the inflow volume of prey‐laden water. The trade‐offs in the relationship between mouth friction drag, area and speed have been illustrated by Potvin and Werth (); we present the estimated open‐mouth friction drag relative to bowhead whales (i.e. scaled by gape area) and put these values in context with their resulting filtration rates (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining prey via an efficient cross-flow filtration system (Potvin & Werth, 2017;Sanderson, Roberts, Lineburg, & Brooks, 2016), accumulated prey must be swallowed; pausing filtration to swallow has been observed in other ram filter feeders ranging in size from basking and whale sharks (Figure 9; Motta et al, 2010;Nelson & Eckert, 2007;Sims, 2000b) to paddlefish (Sanderson, Cech, & Cheer, 1994) and herring, shad, sardines, menhaden and alewife (Sanderson & Wassersug, 1990). Hallacher (1977) and later Sims (2000b) noted pauses in the open-mouth feeding behaviours of basking sharks, with ~3 s interruptions to swallow prey.…”
Section: Previous Descriptions Of Right Whale Diving Behaviour In Deep-mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrodynamic mechanisms by which baleen filters seawater remain unknown, though recent work by Werth and Potvin () and Potvin and Werth () has illuminated the likely filtration process used by balaenids. Their work suggests that right and bowhead whales use cross‐flow filtration rather than sieve, or throughput, filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐flow filtration (CFF) and vortical cross‐step filtration (Sanderson et al, ) have also been identified in bony fishes (Cheer et al, ; Brainerd, ; Sanderson et al, ) and elasmobranchs (Paig‐Tran et al, ; Paig‐Tran and Summers, ). Balaenid whales feature both morphological and behavioral adaptations that create the necessary pressure gradients to enable and support CFF during the continuous forward motion of the animal while feeding (Werth and Potvin, ; Potvin and Werth, ).…”
Section: Introductionmentioning
confidence: 99%